2019
DOI: 10.1155/2019/3453850
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of a Green Supply Chain with One Manufacturer and Two Competing Retailers under Different Power Structures

Abstract: e main objective of this research is to examine the role of power relationship in a two-level green supply chain which is made up of one shared manufacturer and two competitive retailers. We develop six game theory-based models to explore the members' operational decisions in a supply chain taking into account three vertical power structures (Manufacturer Stackelberg, Retailer Stackelberg, and Vertical Nash) as well as two retailers' horizontal power structure (Bertrand or Stackelberg competition). en, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 18 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…According to references [49][50][51][52][53][54][55][56][57][58], Table 2 shows the parameters and their meanings involved in this paper.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…According to references [49][50][51][52][53][54][55][56][57][58], Table 2 shows the parameters and their meanings involved in this paper.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…They pointed out that environmental awareness could improve a firm’s profit in GSCM. Wang et al [ 4 ] studied the effect of government subsidies on members’ revenues in GSCM, and the results showed that they have a positive influence on the selling channel selection. Zhang and Li [ 5 ] discussed the optimal results for a point firm in GSCM and pointed out that the greenness level has a vast impact on the GSCM.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their research showed that the balanced power structure always performs best for the whole SC. Wang et al [19] explored the operational decisions and coordination of a green SC with one manufacturer and two retailers taking into account three vertical power structures VOLUME 4, 2016 This work is licensed under a Creative Commons Attribution 4.0 License. For more information, see https://creativecommons.org/licenses/by/4.0/ This article has been accepted for publication in a future issue of this journal, but has not been fully edited.…”
Section: B Management Of a Supply Chain Under Different Power Structmentioning
confidence: 99%
“…Note that the above-mentioned research looked exclusively at SC pricing decisions or coordination and management insights were gained. In particular, literatures [17], [18] and [19] were similar to this paper, they studied the pricing decisions under three power structures between one manufacturer and two retailers, but none of these considered carbon emissions policy. In this paper, we introduce CT policy into a one-manufacturer and two-retailers SC model, and analyse the influence of CT rate on pricing and enterprise profits.…”
Section: B Management Of a Supply Chain Under Different Power Structmentioning
confidence: 99%